A drug–drug interaction study of ibrutinib with moderate/strong CYP3A inhibitors in patients with B-cell malignancies. Issue 12 (2nd December 2018) - de Jong, Jan; Hellemans, Peter; De Wilde, Severijn; Patricia, Daniel; Masterson, Tara; Manikhas, Georgii; Myasnikov, Alexander; Osmanov, Dzhelil; Córdoba, Raúl; Panizo, Carlos; de Zwart, Loeckie; Snoeys, Jan; et al.
Abstract: This was an open-label, multicenter, phase-1 study to evaluate the drug interaction between steady-state ibrutinib and moderate (erythromycin) and strong (voriconazole) CYP3A inhibitors in patients with B-cell malignancies and to confirm dosing recommendations. During cycle 1, patients received oral ibrutinib 560 mg qd alone (Days 1–4 and 14–18), and ibrutinib 140 mg (Days 5–13; 19–27) plus erythromycin 500 mg tid (Days 5–11) and voriconazole 200 mg bid (Days 19–25). Twenty-six patients (median [range] age: 64.5 [50–88] years) were enrolled. Geometric mean ratio (90% confidence intervals) after co-administration of ibrutinib 140 mg with erythromycin and voriconazole was 74.7 (53.97–103.51) and 143.3 (107.77–190.42), respectively, versus ibrutinib 560 mg alone. The most common (≥20%) adverse events were diarrhea (27%) and neutropenia (23%). The results demonstrate that ibrutinib 140 mg with voriconazole or erythromycin provides exposure within the clinical range for patients with B-cell malignancies.